Factors affecting the application of balanced scorecard to enhance operational efficiency of listed companies: The case of Vietnam - Thu Trang Ta; Thanh Nga Doan; Hoai Nam Tran; Tuan Anh Dam; Trinh Manh Quyen Pham (Cogent Business & Management, 2022)
The study focuses on the factors affecting the application of Balanced Scorecard (BSC) in Vietnamese listed companies, through which they can improve the ability to apply BSC in their businesses. The factors included in the study consist of organizational size, organizational culture, manager’s awareness, accountant’s capability, cost of using BSC, and benefits of using BSC. In addition, the study examines the impact of BSC application on the operational efficiency of listed companies in Vietnam. The authors used the mixed research method combined with Structural Equation Modelling (SEM) to conduct the research. Data were collected from June 2021 to December 2021 from 274 listed companies in the Vietnamese stock market. The research results show that all factors positively influence the application of BSC. Also, the study shows that the higher the level of BSC application, the higher the operational efficiency of enterprises. The authors give some management implications to support enterprises in implementing BSC effectively.